Sexual and physical revictimization in U.S. military veterans. Issue 4 (1st March 2022) - Scoglio, Arielle A. J.; Molnar, Beth E.; Lincoln, Alisa K.; Griffith, John; Park, Crystal; Kraus, Shane W.
Abstract: The present study examined revictimization, defined as sexual or physical assault in adulthood that followed a history of childhood maltreatment. We aimed to identify factors associated with revictimization over time in a group of U.S. military veterans deployed following the September 11, 2001, terrorist attacks (9/11). As revictimization is associated with multiple negative mental health outcomes in the literature, identifying risk and protective factors can aid in the prevention of revictimization and associated poor health outcomes among veterans. In this sample, the proportion of adult revictimization was 2.7% for men, 95% CI [2.0, 3.6] and 22.9% for women, 95% CI [20.5, 25.8]. Using multilevel logistic models, we found that women, β = 2.2, p  < .001; Navy veterans, β = 1.5, p  < .001; and participants who reported posttraumatic stress symptoms, β = 0.2, p  = .028, were at significantly higher risk of revictimization across time compared to nonrevictimized counterparts. Social support while in the military was protective, β = −0.1, p  < .001, against revictimization. In addition, childhood abuse experiences combined with characteristics such as female gender were related to an increased risk of revictimization during and following military service. The findings highlight opportunities for intervention and areas of strength within this population; social connection garnered during military service may serve as a protective factor against revictimization. Future research is needed to examine the role of social support in possibly lowering veterans' risk of revictimization over time, particularly for post‐9/11 veterans struggling with transitioning from military to civilian life.